A Analisis Usaha Peternakan Broiler (Studi Kasus Peternakan X di Kecamatan Upau Kabupaten Tabalong) - Riyadhi, Muhammad Muhammad Riyadhi (JURNAL PENELITIAN PETERNAKAN LAHAN BASAH, 2025)
Abstract This study aims to examine the financial aspects and feasibility of the broiler farming business under a partnership scheme at Farm X in Upau Subdistrict, Tabalong Regency. The components used in this income analysis include production costs, revenue, profit, as well as business feasibility analysis using R/C, B/C, ROI, and BEP. The research was conducted using a purposive sampling method, in which the selected broiler farmer operates at a scale of 4,000 chickens per cycle, with six production cycles per year. The results of the study show that the average production cost per cycle is IDR 151,368,744, revenue is IDR 165,860,280, and profit is IDR 14,491,506. The R/C of this business is 1.09, The B/C is 0.1, ROI is 9%, production BEP is 6,812 kg, and price BEP is IDR 24,190,-. Based on these results, it can be concluded that the broiler business at Farm X in Upau Subdistrict, Tabalong Regency is profitable and feasible.